1995
DOI: 10.1126/science.7716522
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Mammalian Grb2 Adaptor

Abstract: The mammalian growth factor receptor-binding protein Grb2 is an adaptor that mediates activation of guanine nucleotide exchange on Ras. Grb2 binds to the receptor through its SH2 domain and to the carboxyl-terminal domain of Son of sevenless through its two SH3 domains. It is thus a key element in the signal transduction pathway. The crystal structure of Grb2 was determined to 3.1 angstrom resolution. The asymmetric unit is composed of an embedded dimer. The interlaced junctions between the SH2 and SH3 domains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
196
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(209 citation statements)
references
References 28 publications
13
196
0
Order By: Relevance
“…This observed mobility is reminiscent of the dynamic behavior that has been reported between tandem SH2-SH3 domains of Abl kinase (56,57), Hck kinase (52,58), Lck kinase (59), and Src kinase (60). The recent solution structure of the SH3-SH2-SH3 adapter protein Grb2 also demonstrates a lack of rigid domain orientation (61,62). Functionally, this flexibility may be necessary to facilitate binding to many different independent or consolidated phosphotyrosine-containing and proline-rich ligands from disparate components of the signal transduction machinery.…”
Section: Discussionmentioning
confidence: 80%
“…This observed mobility is reminiscent of the dynamic behavior that has been reported between tandem SH2-SH3 domains of Abl kinase (56,57), Hck kinase (52,58), Lck kinase (59), and Src kinase (60). The recent solution structure of the SH3-SH2-SH3 adapter protein Grb2 also demonstrates a lack of rigid domain orientation (61,62). Functionally, this flexibility may be necessary to facilitate binding to many different independent or consolidated phosphotyrosine-containing and proline-rich ligands from disparate components of the signal transduction machinery.…”
Section: Discussionmentioning
confidence: 80%
“…In the other, the conformation of Arg pB5 is altered such that different Arg pB5 H, protons make contact with the Ser PC5 0, and His PD4 Ngl than shown in Figure 4. Finally, these hydrogen bonds are poorly conserved in the two SH2 domains in the crystallographic dimer observed in the structure of Grb2 (Maignan et al, 1995). In one, the distance between His pD4 HE2 and Glu aA6 0 s atoms is 3.4 A, too far for hydrogen bonding, but the other two hydrogen bonds are present.…”
Section: Histidine Pka Values For the Free Plcc Sh2 Domainmentioning
confidence: 99%
“…These included a refined solution structure of the PLCC SH2 domainpY1021 complex (Pascal et al, 1997) based on the previously published structure (PDB filecode 2PLD; Pascal et al, 1994), as well as crystal structures of the N-terminal SH2 domain of Syp phosphatase (Lee et al, 1994), free (PDB filecode I AYD), and in complex with phosphopeptides (PDB filecodes IAYA, lAYB, and IAYC), the SH2 domain of Grb2 (PDB filecode IGRI; Maignan et al, 1995), the Lck SH2 domain-phosphopeptide complex (PDB filecode ILCJ; Eck et al, 1993) and the Src SH2 domain (Waksman et al, 1993), free (PDB filecode ISPR), and phosphopeptidecomplexed (PDB filecode 1SPS).…”
Section: Methodsmentioning
confidence: 99%
“…This analysis, together with predictions based on known SH2 domain structures, 21 suggested that the domain comprises residues 1251-1349. Crystallization trials with the corresponding recombinant domain from S. cerevisiae, Schizosaccharomyces pombe, Candida glabrata, and Homo sapiens resulted in crystals for the C. glabrata SH2 domain, 29 and alignment of amino acid sequences of the Spt6 SH2 domains of C. glabrata (C.g.…”
Section: Structure Determination Of the Spt6 Sh2 Domainmentioning
confidence: 99%